DEVELOPMENT OF BLENDED LEARNING ON ENGLISH LEARNING OUTCOMES IN PJKR STUDY PROGRAM: DEVELOPMENT OF BLENDED LEARNING ON ENGLISH LEARNING OUTCOMES IN PJKR STUDY PROGRAM - RISKA NAHARA SAPUTRI; EPI SUPRIYANI SIREGAR; SITI AMINAH HASIBUAN; NURMAYANA NURMAYANA (English Education Study Program STKIP PGRI Pacitan, 2023)
This study aims to determine the development of blended learning on the results of learning English in PJKR study program. The method used in this research is quasi-experimental or quasi-experimental. The quasi-experimental method is different from the actual experiment. In the quasi-experimental method, it has a control group. The sampling technique used in this research is cluster sample or called group sample. Data collection is the most important part of research. Effective and complete data determine the quality of researchers. In this study the authors used the learning achievement test technique, test, observation and documentation. Based on the results of the research that had been done, the size of the concentration and distribution of the pretest result data for the experimental group were: the largest score was 75 and the smallest score was 36, the mean (mean) was 51.67 , the median is 52, the mode is 40.5 and the standard deviation is 11.91. While the posttest data results, the highest score was 91 and the lowest score was 45, the mean (mean) was 72.8, the median was 76.9, the mode was 77.6 and the standard deviation was 15.58. So, the objectives to be achieved in the learning design have been implemented for that, the blended learning model is able to influence student learning outcomes in English.